Impact Of Using Virtual Reality Technology On The Creative Thinking And Technical Skills In Soccer For Middle School Students - هيثم, فتح الله عبد الحفيظ; بن عبد الله , عبد القادر (Journal of Sport Science Technology and Physical Activities, 2024)
The current research aims to identify the impact of using virtual reality technology on the creative thinking and technical skills in soccer for middle school students inl-Sharkia governorate ,Egypt, The experimental method was used, and applied to the research sample of 30 pupils from the first grade of the middle school and divided into two groups one experimental and on group each one (15) pupils from the first grade, tools included a virtual reality program, physical tests, Torrens creative thinking test and the technical skills tests, the Mean ,standard deviation and T. test were used for data treatment.and the most important results that the virtual reality program has a positive impact on learning and developing the use of virtual reality technology on the technical skills, in soccer for first year middle school students, and there are statistically significant differences ,between the two posttests for each of the experimental, and control groups in the posttests of the creative thinking, and the technical skills, in soccer in favor of the posttests of the experimental group